Arbuscular Mycorrhizal Fungi and Nutrition Determine the Outcome of Competition Between Lolium multiflorum and Trifolium subterraneum - Unger, Stephan; Habermann, Franziska M.; Schenke, Katarina; Jongen, Marjan (Frontiers in Plant Science, 2021)
Arbuscular mycorrhizal fungi (AMF) may affect competitive plant interactions, which are considered a prevalent force in shaping plant communities. Aiming at understanding the role of AMF in the competition between two pasture species and its dependence on soil nutritional status, a pot experiment with mycorrhizal and non-mycorrhizal Lolium multiflorum and Trifolium subterraneum was conducted, with manipulation of species composition (five levels), and nitrogen (N)- and phosphorus (P)- fertilization (three levels). In the non-mycorrhizal state, interspecific competition did not play a major role. However, in the presence of AMF, Lolium was the strongest competitor, with this species being facilitated by Trifolium. While N-fertilization did not change the competitive balance, P-fertilization gave Lolium, a competitive advantage over Trifolium. The effect of AMF on the competitive outcome may be driven by differential C-P trade benefits, with Lolium modulating carbon investment in the mycorrhizal network and the arbuscule/vesicle ratio at the cost of Trifolium.